PEMBUATAN VIRTUAL TOUR SEBAGAI SARANA PEMBELAJARAN PROGRAM STUDI MICE - Mardhiatul Husna; Erwinsyah Simanungkalit; Faulina Faulina (Lambung Mangkurat University, 2021)
Medan State Polytechnic is a vocational education that has D4 and D3 study programs, one of which is the Meeting, Incentive, Converence and Exhibition (MICE) study program. This study program was founded in 2007 until now only has a computer laboratory, language and 6 classrooms and a lecturer room 1. The MICE study program in its learning provides theory and practice with theoretical credits of 58 = 41% and practice of 87 = 59% or 80: 143 hours. So far, students have practiced directly in the field (field study) such as convention halls in hotels andalso the field for the implementation of exhibitions. In current conditions, the event cannot be held, for that the mice study program must prepare a laboratory to support the MICE learning. This laboratory is equipped with equipment to create virtual tours such as the Insta 3600 One R Twin Edition camera and the Oculus Rift S as a Virtual Reality (VR) System, the development of virtual tours using the MDLC (Multimedia Development Life Cycle) method was chosen because MICE students are used to it. designing and implementing events so that students are expected to be able to build and practice learning meetings, conferences, exhibitions in a better and interesting way, meanwhile for incentives students can see virtual tours and create virtual tour incentives. From this research it can be concluded that to be able to build a Virtual Tour is not difficult, it only requires knowledge of how to use the 3600 camera properly and use the VR System so that MICE students who do not have programming knowledge can still build their own Virtual Tour.Keywords: Learning, Virtual Tour, Virtual Reality System, Oculus Rift S, MICEPoliteknik Negeri Medan merupakan pendidikan vokasional yang memiliki program studi D4 dan D3, satu diantaranya program studi Meeting, Insentive, Converence and Exhibition (MICE). Program studi ini berdiri sejak tahun 2007 sampai sekarang hanya memiliki laboratorium komputer, bahasa dan ruangan kelas 6 dan ruangan dosen 1. Program studi MICE dalam pembelajarannya memberikan secara teori dan praktik dengan SKS teori 58=41% dan praktik 87=59% atau jam 80:143. Selama ini mahasiswa melakukan praktik langsung ke lapangan (field study) seperti convention hall di hotel dan juga lapangan untuk pelaksanaan pameran. Dalam kondisi sekarang, event itu tidak bisa dilaksanakan, untuk itu program studi mice harus menyiapkan laboratorium untuk mendukung pembelajaran MICE tersebut. Pada laboratarium ini dilengkapi dengan peralatan untuk membuat virtual tour seperti kamera Insta 3600 One R Twin Edition dan Oculus Rift S sebagai Virtual Reality(VR) System, pengembangan virtual tour mengunakan metode MDLC (Multimedia Development Life Cycle) metode ini dipilih karena mahasiswa MICE sudah biasa merancang dan melaksanakan event sehingga diharapkan mahasiswa dapat membangun dan mempraktikkan pembelajaran Meeting, Conference, Exhibition secara lebih baik dan menarik sementara itu untuk Insentive mahasiswa dapat melihat virtual tour dan membuat virtual tour insentive. Dari penelitian ini dapat disimpulkan untuk dapat membangun Virtual Tour tidaklah sulit hanya diperlukan pengetahuan bagaimana menggunakan kamera 3600 dengan baik dan penggunaan VR System sehingga mahasiswa MICE yang tidak memiliki pengetahuan pemprograman tetap dapat membangun Virtual Tour sendiri.Kata kunci: Pembelajaran, Virtual Tour, Virtual Reality System, Oculus Ridft S, MICE